Review Paper on Microcontroller Based Fire Detection Alarm System - Rao, S. Narsingh; Malakondiah, K (International Journal of Computer Sciences and Engineering, 2025)
This paper presents primarily on a low cost fire search and control system based on smoke and heat identification proposed. It has a combination of electrical / electronic devices / devices working together to identify keeping people through audio or visual media after detecting fire and presence. Fire alarms are used in the context of fire or fire drill. They manually or automatically activated. After fire protection goals are established-usually by referring to the minimum level appropriate model building code, mandatory protection by insurance agencies, and other officials - the Fire Alarm takes on the designer details specific parts, arrangements, and required interfaces to achieve these goals [1]. These sets out various circuits for the paper spot the fire. These alarms can be activated smoke detectors or hot detectors, which detects the fire. Then, it will automatically use a relay send short message service (SMS) to registered mobile numbers. Switch water scratch or solenoid pump spraying water or fire spraying.